A CLINICAL STUDY TO EVALUATE THE EFFICACY OF AMALAKAVLEHA AS RASAYANA IN HEALTHY INDIVIDUALS (AYUSHDHARA, 2020)
Rasayana is one of the eight branches of classical Ayurveda, used for prevention of diseases and prolongation of a healthy life. Rasayana are rejuvenators, nutritional supplements, possess strong anti-oxidant activity and increases Ojas. Rasayana therapy enhances the qualities of Rasa, enriches it with nutrients so one can attain longevity, freedom from diseases, youthfulness, memory, intelligence; excellence in complexion, lustre and sense organs; development of healthy physique and rejuvenation of mind and body. Present study has been designed to evaluate the efficacy of Amalakavleha as Rasayana in healthy individuals. 45 individuals fulfilling the inclusion criteria were randomly selected and divided into two groups. In Group-I, 23 individuals were administered Amalakavleha and in Group-II, 22 individuals were given starch capsules as placebo for 8 weeks. Individuals were thoroughly assessed on various subjective and objective parameters during complete trial period. Group-I individuals showed statistically significant improvement on various treadmill test related parameters like exercise time, maximum work load, VO2 max and rate pressure product, whereas statistically insignificant changes in these parameters were observed in the individuals receiving placebo. In Group-I during TMT, exercise time increased by 8.15% and Group-II had a marginal increase of only 0.30%, rise of 8.97% observed in maximum work load attained in Group-I whereas Group-II individuals showed rise of 1.78%. In Group-I, Vo2 max had 4.10% rise as compared to Group-II, having negligible rise of 0.15%. RPP in Group-I increased by 6.75%, while in Group-II 0.21% change was noticed. These results prove the efficacy and safety of Amalakavleha as Rasayana in healthy individual’s w.r.t. physical and mental health. No untoward effects of therapy were observed in study subjects during the entire trial period.